The criteria to achieving sub-ambient radiative cooling and its limits in tropical daytime - Han, Di (2022)
While radiative cooling has been proven successful in mid-latitude regions to achieve sub-ambient temperatures, the same performance could not be achieved in tropical regions due mainly to the higher solar irradiance and atmospheric radiation. Herein, for the first time, the criteria to achieve sub-ambient temperatures in the challenging conditions of tropical daytime is recommended based on the solar reflectance and infrared emittance of an effective broadband radiative cooler. Briefly, the total solar reflectance of the material should be above 97% with an infrared emittance of over 80% to achieve sub-ambient temperatures. To illustrate, the feasibility of daytime radiative cooling under Singapore's tropical climate is investigated using a radiative cooler that meets these criteria. By having a solar reflectance of 98.4% and infrared emittance of 95% within the 8–13 μm spectrum, sustained daytime sub-ambient temperature of 2 °C can be achieved under direct exposure to solar intensity of 1000 W/m2 and downwelling atmospheric radiation of 450 W/m2. The simulated cooling power limit was around 35 W/m2, with the potential to provide over 30 MJ/m2 of cooling energy per month.